Diagnosis of Drowning and the Value of the Diatom Test in Veterinary Forensic Pathology - Piegari, Giuseppe; De Biase, Davide; d'Aquino, Ilaria; Prisco, Francesco; Fico, Rosario; Ilsami, Raffaele; Pozzato, Nicola; Genovese, Angelo; Paciello, Orlando (Frontiers in Veterinary Science, 2019)
The detection of diatoms into the organs is considered an important “biological marker” for the diagnosis of drowning in human pathology, but it still has a high possibility for false positive results. The aims of this study were: 1) to evaluate the contribution of pathological examination in drowning cases and 2) to investigate the differences in the number and location of diatoms between animals who died in drowning and non-drowning conditions. For these purposes, thirty dead adult dogs were selected for the study and subdivided into 5 groups. The group A comprised 6 cadavers dead for drowning; the group B comprised 6 control animals; the groups C, D and E comprised 6 animals dead for causes other than drowning and subsequently immersed in water for 24, 48 and 72 hours respectively. On each animal, a complet macroscopic and histological examination and diatom test were performed. Diatoms test and quantification were also performed on drowning mediums. Pathological findings of the animals in the group A showed pulmonary congestion, oedema and haemorrages in the lung. However, similar injuries were also observed in control and experimentally submerged cadavers. In contrast, we observed a statistically differences between drowning animals and all experimentally submerged groups and control animals regarding diatom numbers recovered from organ tissue samples (p<0.05). Therefore, these findings suggest that the number of diatoms may be used as a valid tool to differentiate animals who died in drowning and non-drowning conditions, even if the latter were found in an aquatic environment.